2018
DOI: 10.1002/jper.17-0684
|View full text |Cite
|
Sign up to set email alerts
|

Platelet indices (mean platelet volume and platelet distribution width) have correlations with periodontal inflamed surface area in coronary artery disease patients: A pilot study

Abstract: The results of the present study highlight some blood parameters (PDW, RDW, and MPV) in CAD patients with/without periodontitis in terms of the relationship between inflammatory diseases and their significant low and moderate correlations with PISA values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 47 publications
2
27
1
Order By: Relevance
“…In our study, PISA values were consistent with the current classification for periodontal diseases 22 (as well as with the former CDC-AAP classification), 24 , 25 and increased with periodontal disease presence and increased severity. When compared to the other studies, 4 - 6 the higher PISA values reported in our study may be explained by the periodontitis generalized involvement of our groups. Another important finding suggests that gingivitis can cause as much systemic inflammatory burden as stage I periodontitis: the overlap in PISA values and the positive strong correlations between PISA and pro- and anti-inflammatory biomarker levels in gingivitis and stage I periodontitis groups.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…In our study, PISA values were consistent with the current classification for periodontal diseases 22 (as well as with the former CDC-AAP classification), 24 , 25 and increased with periodontal disease presence and increased severity. When compared to the other studies, 4 - 6 the higher PISA values reported in our study may be explained by the periodontitis generalized involvement of our groups. Another important finding suggests that gingivitis can cause as much systemic inflammatory burden as stage I periodontitis: the overlap in PISA values and the positive strong correlations between PISA and pro- and anti-inflammatory biomarker levels in gingivitis and stage I periodontitis groups.…”
Section: Discussioncontrasting
confidence: 66%
“…When compared to the other studies, [4][5][6] To the best of our knowledge, this is the first study to investigate serum and salivary NGAL levels considering different periodontal diseases and severity. We found all periodontal parameters and PISA values to proportionally increase with increased disease severity and NGAL levels.…”
Section: Groupsmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, PDW has also been regarded as a more concrete parameter for platelet activation than MPV, as it does not increase during simple platelet swelling [34, 35]. Accordingly, some studies have suggested a potential relationship between PDW and CAD [36, 37]. Our study showed that PDW was an independent risk factor for plaque rupture as well as TCFA occurrence in NSTE-ACS patients.…”
Section: Discussionsupporting
confidence: 50%
“…The link between periodontitis and leukocytosis is well documented [35][36][37][38][39][40]. This result is expected given the infectious nature of periodontitis where bacteria invade the periodontal tissues via the ulcerated epithelium, and leukocytes, in particular neutrophils, are triggered towards the periodontal injury [40][41][42].…”
Section: Discussionmentioning
confidence: 92%